Firm-specific news and idiosyncratic volatility anomalies: Evidence from the Chinese stock market - Hoang Van Hai (Cogent Economics & Finance, 2022)
In this paper, we examine the relationship between idiosyncratic volatility and future returns around the firm-specific news announcements in the Chinese stock market following. The results show that the pricing of non-news idiosyncratic volatility is more strongly negative compared to news idiosyncratic volatility. Such findings imply that limited arbitrage cannot fully explain the negative pricing of idiosyncratic volatility in the Chinese stock market. These results are robust after controlling for several well-known variables, such as market beta, firm size, book-to-market, momentum, liquidity, and maximum return. However, after adjusting by additional macroeconomic variables, the Chinese four-factor model and the salience trading volume factor, the average returns on zero-investment IVOL and non-news IVOL portfolios turn out to be insignificant, indicating that they may be one driver of the IVOL puzzle in the Chinese stock market.
Keywords: G12; G17; G11; 330; anomalies; Chinese stock market; firm-specific news; idiosyncratic volatility; news idiosyncratic volatility; non-news idiosyncratic volatility